2017
DOI: 10.1212/cpj.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Timed up and go test at tap test and shunt surgery in idiopathic normal pressure hydrocephalus

Abstract: An improvement of 5 seconds was a useful threshold of TUG time at the tap test for predicting a ≥10-second improvement 12 months after shunt surgery, rather than the percent improvement of TUG time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…The functional assessment was performed in the Rehabilitation Medicine Department of Elias University Hospital in Bucharest and included the Timed Up and Go test – 3 meters version (TUG) (3 times means) [ 11 ], the 10m walking test at the self-chosen comfortable speed [ 15 ] and the Berg Balance Scale [ 16 ]. The study compares 24h pre-surgery assessment results with one-month follow-up after surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional assessment was performed in the Rehabilitation Medicine Department of Elias University Hospital in Bucharest and included the Timed Up and Go test – 3 meters version (TUG) (3 times means) [ 11 ], the 10m walking test at the self-chosen comfortable speed [ 15 ] and the Berg Balance Scale [ 16 ]. The study compares 24h pre-surgery assessment results with one-month follow-up after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…A pre-post TT difference of 3.985 seconds in TUG is a predictor of positive response to the surgical intervention in NPH [ 10 ]. A TUG time shortened by 5 seconds or more after a TT predicts a 40-60% expectancy of improvement in TUG time at 12 months after shunt surgery, by more than 10 seconds or 5 seconds, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TUG does not require a trained physical therapist and can be administered by clinical staff in approximately 3 minutes. It is a reliable predictor of shunt outcome in NPH patients [38][39][40]. In our analysis, the TUG was significantly related to detailed measures of balance, endurance, and gait velocity.…”
Section: Discussionmentioning
confidence: 60%
“…The international idiopathic NPH guideline treats aqueductal stenosis, long-standing overt ventriculomegaly syndrome, and non-communicating hydrocephalus as other hydrocephalus disorders, and clearly exclude them from the category of idiopathic NPH ( 25 ). Although there are numerus articles reporting good outcomes of shunt surgery for idiopathic NPH ( 10 17 ), many neurosurgeons and neurologists still have the negative impression that idiopathic NPH is difficult to treat with a shunt surgery ( 26 , 27 ). This divergence of opinions might be due to confusing classifications of idiopathic and adult-onset congenital NPH.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies in robust diagnostic criteria for idiopathic NPH have shown the beneficial effects of shunting procedures for a patient with idiopathic NPH ( 10 17 ). However, some conservative experts strongly believe that shunt implantation is not effective for a patient with idiopathic NPH from their bitter experiences.…”
Section: Introductionmentioning
confidence: 99%